2022
DOI: 10.1002/app.53189
|View full text |Cite
|
Sign up to set email alerts
|

Tension responses of carbon black filled rubbers at intermediate and high strain rates: Experimental investigation and modeling

Abstract: The uniaxial tensile stressstrain responses of carbon black filled rubbers were experimentally investigated at various strain rates of 0.001, 0.05, 2.5 and 400 s À1 . A conventional hydraulically driven material testing system, an intermediate strain-rate testing system and a split-Hopkinson tension bar were respectively utilized to carry out the monotonic tensile loadings at quasi-static, intermediate and high strain rates. A complete experimental strategy for intermediate strainrate testing of rubber-like ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It can be found that the values of stiffness and nominal stress at a given elongation increase with increased strain rate. Liu et al [ 21 ] studied tensile stress–strain responses of carbon black filled rubbers. It can be found that modulus and stress at a given strain increased with increasing strain rate.…”
Section: Introductionmentioning
confidence: 99%
“…It can be found that the values of stiffness and nominal stress at a given elongation increase with increased strain rate. Liu et al [ 21 ] studied tensile stress–strain responses of carbon black filled rubbers. It can be found that modulus and stress at a given strain increased with increasing strain rate.…”
Section: Introductionmentioning
confidence: 99%